Design for Local Web Shear at Brace Connections: An Adaptation of the Uniform Force Method - Sabelli, Rafael; Saxey, Brandt; Li, Chiao-Hsien; Thornton, William A. (Engineering Journal, 2021)
Recent literature has examined local shear forces in beams in chevron braced frames (Fortney and Thornton, 2015). Subsequently, design methods based on optimal stress distributions to address these shears were developed (Sabelli and Arber, 2017; Sabelli and Saxey, 2021). This paper extends those design methods to gusset connections at columns, utilizing the adaptability of the Uniform Force Method to facilitate design to reduce required member shear strength. The design model presented reduces the required member shear strength required, as compared to the conventional application of the Uniform Force Method. The model allows for redistribution of force from the beam interface to the column interface using a “bypass method,” as well as utilizing the gusset plate as part of a moment connection using the “haunch method.” Finite element analyses are used to confirm the adequacy of a design employing these methods.